Strategi Pencegahan Penyakit Kronis melalui Micro Workouts dan Aktivitas Harian Modern - Sulton Hidayat; Febrian Saputra; Bambang Kusuma Hadi; Pandu Wira (Journal of Medical and Health Science, 2025)
Chronic disease is a major health problem that continues to increase in line with changes in modern lifestyles, characterized by low physical activity and high levels of sedentary behavior. The current approach to chronic disease prevention has been dominated by structured exercise, which in practice is often difficult to implement consistently due to time constraints and the demands of daily activities. This study aims to comprehensively examine chronic disease prevention strategies through micro-workouts and modern daily activities as a more adaptive and sustainable approach to physical activity. This study used a systematic literature review method with a narrative synthesis of open-access journal articles published in the last ten years. The analysis was conducted by grouping research findings based on key themes, including the relationship between physical activity and chronic disease, the effectiveness of micro-workouts, the role of modern daily activities, and factors supporting and inhibiting implementation. The study results indicate that consistent, short-duration physical activity can provide significant health benefits, including improved cardiovascular health, metabolic control, and reduced sedentary behavior. Modern daily activities have been shown to increase total accumulated physical activity without the need for structured exercise. This study concludes that the integration of micro workouts and modern daily activities is a realistic, effective, and appropriate chronic disease prevention strategy that is in line with the lifestyle characteristics of modern society, and has the potential to support promotive and preventive efforts in public health.